Reflexões de uma professora sobre sua trajetória de formação e atuação docente - SILVA, Maria Lindalva Alves da (2023)
This descriptive memorial of teaching practice aims to meet the requirement established in the Course Completion Work (TCC), whose theme is “Reflections of a teacher on her trajectory of training and teaching performance”. The objective is to present reflections on my teaching career, highlighting relevant points about the trunk of my memories, from my educational path as a student to my professional activities as a teacher. The respective account of my educational and teaching experience is based on a reflective narrative, anchored in a bibliographical review, where it was possible to analyze ideas and thoughts of different authors that dialogue with the theme. The results of this memorial highlighted the difficulties and challenges encountered during my journey, through memories that referred to me as experiences lived to get to teaching. As an educator, then, I can say that everything contributed so that I could acquire new knowledge during my school and professional career, understanding that initial and continuing education should be part of the life of any educator who wants to improve their practical and theoretical skills, confident, like that, with the classroom.